2013
DOI: 10.1111/bph.12014
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological modulation of the endocannabinoid signalling alters binge‐type eating behaviour in female rats

Abstract: Background and Purpose Binge eating disorder (BED) is characterized by excessive food intake during short periods of time. Recent evidence suggests that alterations in the endocannabinoid signalling could be involved in the pathophysiology of BED. In this study, we investigated whether pharmacological manipulation of endocannabinoid transmission may be effective in modulating the aberrant eating behaviour present in a validated rat model of BED. Experimental Approach Binge‐type eating was induced in female rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 95 publications
(126 reference statements)
4
19
0
Order By: Relevance
“…Although the usefulness of rimonabant in the treatment of obesity has been debated, it is found to be effective in the treatment of BE [19,20]. In the present study, acute treatment with rimonabant, prior to the BE, significantly decreased consumption of HFSPD.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…Although the usefulness of rimonabant in the treatment of obesity has been debated, it is found to be effective in the treatment of BE [19,20]. In the present study, acute treatment with rimonabant, prior to the BE, significantly decreased consumption of HFSPD.…”
Section: Discussionsupporting
confidence: 44%
“…Daily [18,33,34] or even alternate day [35,36] access to palatable diet for 2-h has been shown to produce BE in rats. However, it is suggested that development of binging is enhanced and remain stable for longer period when it is offered only 3 times per week than for 2-h each day [19,35]. In addition, when the palatable diet is comprised of sugar and fat, daily or alternate day access increases binging behavior to the same degree [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although two small clinical trials did not show Δ9-THC efficacy 176 a larger trial demonstrated small but significant weight gain in women with severe anorexia nervosa following 4 weeks treatment with Dronabinol 188 . Conversely, in binge eating disorder the CB 1 R antagonist Rimonabant significantly reduces binge eating and promotes weight loss with only modest presentation of psychiatric side effects 189, 190 .…”
Section: Endocannabinoid Signaling In Addictionmentioning
confidence: 99%
“…For instance, chronic administration of rimonabant reduced feeding behavior in an animal model of binge eating disorder (Scherma et al 2013) and the same drug was able to decrease body weight and binge eating behavior in obese patients affected by binge eating disorder (Pataky et al 2013). In contrast, Verty and collaborators were able to demonstrate that Δ 9 -THC attenuated weight loss in a rodent model of activity-based anorexia through a mechanism that likely involves a decrease in energy expenditure (Verty et al 2011).…”
mentioning
confidence: 99%